Infant fatality case with excessive chylous ascites. (May 2018) - Idota, Nozomi; Nakamura, Mami; Tojo, Misa; Ichioka, Hiroaki; Shintani-Ishida, Kaori; Ikegaya, Hiroshi
Highlights: An 11-month-old boy with abdominal distention was found dead at his home. As he had massive chylous ascites and many bruises, it was suspected he was abused. Most of causes of chylous ascites in infant and child are congenital. Chylous ascites caused by blunt trauma, including child abuse, is rare. Chylous ascites in infants and children can be a sign of child abuse. Abstract: An 11-month-old boy with marked abdominal distension was found dead in the prone position at home. Since there were many bruises in the non-protruding regions of the head, face, and abdomen, a medicolegal autopsy was performed the following day. The boy was smaller than average (height: 68.5 cm; weight: 7.8 kg); his extremities were thin; and his abdomen was remarkably bulging. Chylous ascites (1600 mL) was observed in the peritoneal cavity and chylous pleural effusion (left: 5 mL; right: 10 mL) in the thoracic cavity. A fibrous induration, approximately 2.0 × 1.5 cm in size, was observed in the root of the small bowel mesentery. Congenital chylothorax and chylous ascites were suspected. However, the remarkably withered thymus and an old injury in the superior labial frenulum suggested that the chylous ascites may have been further deteriorated by injuries sustained during physical abuse. Examination suggested that the death was sudden. Thus, we inferred that the cause of death was circulatory and respiratory failure due to excessive chylous ascites. Among the reported cases of chylous ascites in pediatric patients, some patients experiencing abuse were identified on the basis of their chief complaints of vomiting or abdominal distension. Medical and child welfare staff should be made aware of this information.